THE RELATIONSHIP BETWEEN NUTRITIONAL STATUS AND BREAKFAST HABITS ON ACADEMIC ACHIEVEMENT IN CHILDREN ELEMENTARY SCHOOL SDN SUKOREJO SIDAYU GRESIK - Ningsih, Betty Cahya; Rahma, Amalia; Ariestiningsih, Eka Srirahayu (Ghidza Media Jurnal, 2024)
Breakfast is an important activity before carrying out activities in the morning and contributes around 15% - 30% of daily calorie needs. Breakfast starts from 06.00 until 09.00 in the morning. This study aims to determine the relationship between nutritional status and breakfast habits in elementary school children at SDN Sukorejo Sidayu Gresik. This research was conducted on 33 students in grades V and VI. The measuring tools used in this research were questionnaires, report card grades, and anthropometric data. Data analysis was carried out using the Spearman Rank test. Results: (51,5%) of respondents often consumed breakfast habits and (48,5%) respondents rarely consumed breakfast habits. The results show that there is no relationship between nutritional status and academic achievement (sig of 0.962). And there is no relationship between breakfast habits and academic achievement (sig of 0.357). So it can be concluded that respondents with breakfast frequency categories are often spread across the good and fair performance categories.